2014
DOI: 10.1007/s12020-014-0396-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the effects of high-fat diets on DHEA-treated rats

Abstract: Several studies have investigated the beneficial effects of dehydroepiandrosterone (DHEA) on lipid and glucose metabolism. However, many of these studies are inconclusive about the effects of DHEA administration on metabolic disorders, and there appear to be sex-related differences in the effects of DHEA treatment. Few animal studies have addressed the effects of DHEA on diet-induced metabolic disorders. The present study sought to ascertain whether sex differences exist in the effects of a high-fat diet (HFD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Blood vessels begin to change in the early stages of BioScience Trends Advance Publication P4 decreased by about 20% after receiving DHEA (25 mg/d) for 12 months. A similar finding was noted in another study (45). However, one study (46) found that administration of DHEA does not change blood lipid parameters, which is consistent with the results of a previous study by the current authors (47).…”
Section: Pathogenesis Of Assupporting
confidence: 91%
“…Blood vessels begin to change in the early stages of BioScience Trends Advance Publication P4 decreased by about 20% after receiving DHEA (25 mg/d) for 12 months. A similar finding was noted in another study (45). However, one study (46) found that administration of DHEA does not change blood lipid parameters, which is consistent with the results of a previous study by the current authors (47).…”
Section: Pathogenesis Of Assupporting
confidence: 91%
“…Males have higher fasting glucose levels than females in rodents and humans and are more likely to suffer changes in glucose metabolism with weight gain . However, the increased glycaemia observed in males on the HFD was not associated with weight gain, suggesting a direct dietary effect.…”
Section: Discussionmentioning
confidence: 96%
“…It is probably due to widely reported gender differences of the hepatic phenotype in mouse models of postweaning diet-induced obesity (DIO) 16, 2028 , low dose of aspirin has been previously studied only in male rodents with HF-diet and is reported to reduce the serum lipid content and inhibited the hepatic inflammation 12, 13 . There is unfortunately zero information about aspirin on modulating the lipid metabolism in female mice.…”
Section: Discussionmentioning
confidence: 99%